Study of Quality Comparison of Local Wood Between Laboratory Test Results with Analysis of SNI 2847-2002 and SNI 7973-2013 - Trinugroho, Suhendro (Prosiding Simposium Nasional Rekayasa Aplikasi Perancangan dan Industri, 2020)
Wood is one of Indonesia's natural resources which is a construction element that is easily accessible and available in relatively large quantities. In the construction section, wood is widely used in every function of the building, from preparation to finishing. The research this time aims to determine the strength / quality value of whole wood test results in the laboratory with wood quality based on SNI 2847-2002 and SNI 7973-2013. Types of tests carried out include parallel tensile strength testing, compressive strength parallel to fibers, flexural strength and shear strength. The test objects for each test were 3 pieces with 5 kinds of wood. The wood is Sengon, Bangkirai, Kruwing, Kamper, and Jackfruit from Solo Raya. The results of mechanical testing in the laboratory are compared with the SNI 2847-2002 analysis starting from 14.48% to 87.07%, and with SNI 7973-2013 analysis from 5.30% to 26.39%. From these results provide knowledge that the use of SNI 7973-2013 analysis is closer to the results of mechanical testing in the laboratory than the use of SNI 2847-2002 analysis.